2023
DOI: 10.1089/aid.2022.0054
|View full text |Cite
|
Sign up to set email alerts
|

HIV Incidence, Recent HIV Infection, and Associated Factors, Kenya, 2007–2018

Abstract: Nationally representative surveys provide an opportunity to assess trends in recent human immunodeficiency virus (HIV) infection based on assays for recent HIV infection. We assessed HIV incidence in Kenya in 2018 and trends in recent HIV infection among adolescents and adults in Kenya using nationally representative household surveys conducted in 2007, 2012, and 2018. To assess trends, we defined a recent HIV infection testing algorithm (RITA) that classified as recently infected (<12 months) those HIV-positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…This finding was unexpected since, in the last decade, most studies (19,20) have indicated that old age (>65) is associated with an increased incidence of community-acquired pneumonia. One possibility could be the presence of underlying comorbidity among participants that predisposes the young age to community pneumonia, given that HIV infections are regarded as high in the setting of the study (21). Another possible explanation is that the study period (March to December) consisted of the winter season, which is often associated with sporadic respiratory infections (22).…”
Section: Discussionmentioning
confidence: 99%
“…This finding was unexpected since, in the last decade, most studies (19,20) have indicated that old age (>65) is associated with an increased incidence of community-acquired pneumonia. One possibility could be the presence of underlying comorbidity among participants that predisposes the young age to community pneumonia, given that HIV infections are regarded as high in the setting of the study (21). Another possible explanation is that the study period (March to December) consisted of the winter season, which is often associated with sporadic respiratory infections (22).…”
Section: Discussionmentioning
confidence: 99%